212k views
0 votes
Evaluate this question

Evaluate this question-example-1

1 Answer

2 votes

Answer:

d.

Explanation:


\bigg( (16)/(49) \bigg)^{ - (3)/(2) } \\ \\ = \bigg( (49)/(16) \bigg)^{ (3)/(2) } \\ \\ = \bigg( \frac{ {7}^(2) }{ {4}^(2) } \bigg)^{ (3)/(2) } \\ \\ = \bigg( \frac{ {7}}{ {4} } \bigg)^{ (2 * 3)/(2) } \\ \\ = \bigg( \frac{ {7}}{ {4} } \bigg)^( 3) \\ \\ = (343)/(64) \\

User Jon Mitchell
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.